STRATEGI PEMASARAN BERAS PADA “CV. BERKAT PADAELO” DI KELURAHAN BAKUNG KECAMATAN BATUI KABUPATEN BANGGAI - Ruslan A Zaenuddin; Ardiansyah Ardiansyah; Ambo Abd. Kadir Pakanyamong; Dian Puspapratiwi; Taufik Bidullah (Fakultas Pertanian Universitas Tompotika Luwuk, 2022)
Efforts to maintain a competitive advantage require long-term planning. The analysis used to identify the company's strategic position in the industry, one of which uses a SWOT analysis tool. A marketing strategy is needed because of the increasingly widespread growth and increasingly fierce market competition. This situation of course forces entrepreneurs to use various methods in their marketing strategy. The objectives of this study were to determine Strengths, Weaknesses, Opportunities, Threats to rice marketing at CV. Berkat Padaelo in Bakung Urban Village, Batui District, Banggai Regency. Based on the results of scoring internal factors and external factors, the highest score obtained was the SO (Strengths-Opportunities) strategy of 4.6, the ST strategy (Strengths-Treats) of 3.92, the WO Strategy (Weaknesses-Opportunities) of 2.67, while the lowest is found in the WT (Weaknesses-Threats) strategy of 1.99. SO Strategy (Strengths-Opportunities) of 4.6, is a situation that is very profitable for respondents to have the strength to take advantage of existing opportunities, namely: Strategic Location, Quality Production, Modern Machine Tools, Own Capital, Farmer's Trust, Availability of raw materials, Market support , Support for cooperation with buyers, There is relatively extensive warehousing support, There is support for a skilled workforce.